Design and Evaluation of an Inquiry-oriented Genetics Program using a Multidimensional Conceptual Change Perspective - Coon , Martin (Curtin University, 2019)
A multidimensional conceptual change perspective was used to explore the problem of low student performance in science. An inquiry-oriented intervention was developed and evaluated for effectiveness using educational design research. Results indicate the intervention was responsible for increases in both teacher and student outcomes. The intervention was refined and a plan for broad dissemination explored. A multidimensional conceptual change perspective proved to be an effective referent in the design and evaluation of the intervention.